Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1063/1.2753160
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and segmental dynamics of rodlike molecules by fluorescence correlation spectroscopy

Abstract: The dynamics of weakly bending polymers is analyzed on the basis of a Gaussian semiflexible chain model and the fluorescence correlation spectroscopy (FCS) correlation function is determined. Particular attention is paid to the influence of the rotational motion on the decay of the FCS correlation function. An analytical expression for the correlation function is derived, from which the averaged segmental mean square displacement can be determined independent of any specific model for the polymer dynamics. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 71 publications
(128 reference statements)
2
54
0
Order By: Relevance
“…2(b). At low Pe, we find the well-know dependence τ n /τ 1 ∼ (2n − 1) −4 valid for passive semiflexible polymers [52,56,60]. With increasing Pe, the ratio τ n /τ 1 shifts to larger values, and for Pe 50 the small-mode-number relaxation times 050001-4 .…”
Section: Results: Relaxation Timesmentioning
confidence: 80%
See 1 more Smart Citation
“…2(b). At low Pe, we find the well-know dependence τ n /τ 1 ∼ (2n − 1) −4 valid for passive semiflexible polymers [52,56,60]. With increasing Pe, the ratio τ n /τ 1 shifts to larger values, and for Pe 50 the small-mode-number relaxation times 050001-4 .…”
Section: Results: Relaxation Timesmentioning
confidence: 80%
“…Figure 4 displays MSDs of flexible and semiflexible polymers. For passive polymers, we find the well-known Rouse dependence √ t for flexible polymers [59] and the dependence t 3/4 for semiflexible polymers [56,61,62] at t/τ 1 1. In the presence of activity, the diffusivity is significantly enhanced, as already noted before [23,41,63].…”
Section: -5mentioning
confidence: 99%
“…with the persistence length l p . [26,27] In the following, we will neglect the bond term, i.e., the term with the second derivative and focus on bending stiffness only. The expansion…”
Section: Continuum Modelmentioning
confidence: 99%
“…In a recent paper, Shusterman et al [6] introduced an analysis method for FCS data, which they used to analyze the nanoscale conformational dynamics of single-and double-stranded DNA, reporting Zimm instead of Rouse dynamics for the studied molecules. This finding has spurred considerable theoretical work in an effort to explain this unexpected result [7][8][9]. Meanwhile, the analysis method of Shusterman et al has found widespread application in FCSbased studies of polymer dynamics Ref.…”
mentioning
confidence: 99%